Analysis of Genetic Polymorphism of Bitter Taste Receptor TAS2R38 and TAS2R46, and Its Relationship with Eating and Drinking Habits in Japanese ToMMo Subjects - SHIRAKAWA, Hitoshi; YAMAKI, Michiko; SHOJI, Noriaki; SAITO, Hiroki; KOMAI, Michio; NAGASAKI, Masao; SATOH-KURIWADA, Shizuko; GOTO, Tomoko; MIMORI, Takahiro; SUZUKI, Kichiya; SUZUKI, Yoichi; ISONO, Kunio (Journal of Nutritional Science and Vitaminology, 2023)
Human type 2 taste receptor (TAS2R) genes encode bitter-taste receptors that are activated by various bitter ligands. It has been said that TAS2R38 may detect bitter substances and then suppress their intake by controlling gustatory or digestive responses. The major haplotypes of TAS2R38 involve three non-synonymous, closely-linked single-nucleotide polymorphisms (SNPs), leading to three amino acid substitutions (A49P, V262A and I296V) and resulting in a PAV or AVI allele. The allele frequency of AVI/PAV was 0.42/0.58 in this study. The genotype frequency distributions of TAS2R38 were 18.32%, 46.95% and 33.95% for AVI/AVI, AVI/PAV and PAV/PAV, respectively, and were in Hardy-Weinberg equilibrium. Five haplotype combinations of minor alleles were identified: AVI/AAV, AVI/AVV, AAI/PAV, AVI/PVV, AVI/AAI, with corresponding frequencies of 0.49%, 0.10%, 0.10%, 0.05%, 0.05%, respectively, in 2,047 Japanese Tohoku Medical Megabank Organization (ToMMo) subjects (2KJPN). The 16 subjects with these minor alleles were excluded from the questionnaire analysis, which found no significant differences among the major TAS2R38 genotypes (AVI/AVI, AVI/PAV and PAV/PAV) in the intake frequency of cruciferous vegetables or in the frequency of drinking alcohol. This result differs from previous data using American and European subjects. This is the first study to analyze the relationship between TAS2R38 genotype and the eating and drinking habits of Japanese subjects. It was also shown that there were no relationships at all between the genetic polymorphism of TAS2R46 and the phenotypes such as clinical BMI, eating and drinking habits among the 3 genotypes of TAS2R46 (∗/∗, ∗/W, W/W) at position W250∗ (∗stop codon).